Literasi Tarian Kelik Lang Dalam Acara Pernikahan Dikalangan Penari Kelurahan Pulau Temiang Kecamatan Tebo Ulu Kabupaten Tebo Provinsi Jambi - Fitri Indriyani; Masyrisal Miliani (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
Introduction. The purpose of this study was to determine the literacy of the dancers of Pulau Temiang Village in accessing the Kelik Lang dance, to determine the dancers of Pulau Temiang Village in evaluating Kelik Lang dance and to determine the dancers of Pulau Temiang Village in using the Kelik Lang dance. Research methods. This study uses a qualitative method with a descriptive approach. Discussion result. The results of this study indicate that in accessing literacy the Kelik Lang dance is included in the Competent level of ability, in defining information needs, but it is still not very complete to know information about Kelik Lang dance both from the meaning and movements in the Kelik Lang dance. But some informants already know enough information about the Kelik Lang dance both from the motion and the meaning in the movement. In searching for information on the Kelik Lang dance, all informants are more dominant in getting information about the Kelik Lang dance more searching from the internet, the dancers from the Pulau Temiang Village in evaluating Kelik Lang dance literacy in the Competent level of ability, in assessing Kelik Lang dance information, using information and sharing the information they get to the community in Pulau temiang Village or outside the Village. The dancers have evaluated the information they have obtained from parents or dance teachers or the internet. In the information organization they have not categorized the information they are looking for. The dancers of Pulau Temiang Village in using the Kelik Lang dance enter the level of Proficient ability, in using information the dancers have presented/presented well, namely preparing with practice long before they perform, wearing uniform costumes, and also preparing musical instruments to accompany the dance. In communication and the use of information ethics, Kelik Lang dancers already understand the use of ethics in conveying Kelik Lang information, but Kelik Lang dancers have not disseminated and communicated information to other people or the public. Conclusions and suggestions. Based on the research that has been done about the literacy of the Kelik Lang dance in the wedding ceremony among dancers in the temiang island village, tebo ulu district, tebo district, Jambi province. In accessing information, dancers are expected to be more broad in seeking information from the media, evaluate information more thoroughly, carefully and more literately. Using information, dancers are expected to often communicate/socialize to others.